Children's Innocence Discourse: Are They Vulnerable? - Hanifah, Siti (Muttaqien Publishing, Pusat Penelitian dan Pengabdian kepada Masyarakat STAI DR.KH.EZ.Muttaqien Purwakarta, 2024)
Early childhood is often perceived as a time of innocence in their perception of the world; however, questions arise about whether this innocence truly makes them vulnerable to risky situations. This research aims to provide a deeper understanding of the factors influencing children's innocence and its connection to their vulnerability to risky situations. The research method employed is a Systematic Literature Review. Data analysis techniques involve thematic data analysis. Article collection was conducted for three months from October to December 2023, utilizing secondary data. The secondary data sources consist of high-quality journal articles nationally and proceedings with a predefined focus. These articles were obtained from the Google Scholar database using keywords such as